Head and neck oncological ablation and reconstruction in the COVID-19 era – our experience to date. Issue 8 (October 2020) - Butler, Daniel; Davies-Husband, Cameron; Dhanda, Jagtar; Francis, Ian; Gulati, Aakshay; Kapoor, Karan; Newman, Laurence; Norris, Paul; Sadiq, Zaid; Surwald, Christian; Upile, Navdeep; Vorster, Tim; et al.
Abstract: The COVID-19 pandemic has caused unprecedented disruption to the routine operations of healthcare services across the world. As the potential duration of the pandemic remains uncertain, the need to develop strategies to continue urgent elective services has received increasing attention. A solution adopted in the Kent, Sussex and Surrey area of England has been to create COVID-19-protected cancer hubs. The Queen Victoria Hospital is the designated hub for head and neck cancer services in the area. We report on the evolution of the head and neck cancer care pathway and standard operating protocols put in place and how these have combined both national guidelines and local problem solving. It is hoped that our experience can help guide other centres as they re-establish head and neck cancer services during the ongoing pandemic.